2013
DOI: 10.1007/s10815-013-0077-z
|View full text |Cite
|
Sign up to set email alerts
|

Determining an anti-mullerian hormone cutoff level to predict clinical pregnancy following in vitro fertilization in women with severely diminished ovarian reserve

Abstract: Purpose Serum anti-Mullerian hormone (AMH) levels estimate ovarian reserve. The purpose of this study was to identify a minimum serum AMH level that correlates with acceptable clinical pregnancy rate (CPR) in women with severe diminished ovarian reserve (DOR) undergoing in vitro fertilization (IVF). Methods(s) A historical cohort of severe DOR participants (age ≥35) with day 3 FSH of >10 ng/mL were included (n =120). Participants were categorized into 3 groups: AMH <0.2 (Group 1, n =38), AMH=0.2-0.79 (Group 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 26 publications
2
23
0
4
Order By: Relevance
“…We know that a correlation exists between AMH levels and oocyte retrieval numbers, antral follicle count, pregnancy rates and birth rates. The role of AMH as an efficient prognostic factor in determining the probability of pregnancy has been largely discussed [5][6][7][8]. Revelli et al [9] calculated that in women with very low circulating AMH level the probability of pregnancy was significantly affected by age.…”
Section: Eu)mentioning
confidence: 99%
“…We know that a correlation exists between AMH levels and oocyte retrieval numbers, antral follicle count, pregnancy rates and birth rates. The role of AMH as an efficient prognostic factor in determining the probability of pregnancy has been largely discussed [5][6][7][8]. Revelli et al [9] calculated that in women with very low circulating AMH level the probability of pregnancy was significantly affected by age.…”
Section: Eu)mentioning
confidence: 99%
“…Poor ovarian response after in vitro fertilization (IVF) treatments is a challenge for both patients and their clinicians (Karande 2003). Clinicians are constantly seeking ways to improve the outcome of poor responders, especially in older women with severely diminished ovarian reserve (DOR) (Gleicher et al 2010;Merhi et al 2013). It is not uncommon to have no oocytes retrieved in women with severe DOR undergoing IVF, especially when there is very little follicular growth (Karande 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Women with serum AMH below the 10th percentile of the general population have been reported to have an overall low global chance of achieving a viable pregnancy [9], and some authors suggested 0.15-0.2 ng/ml as the AMH cutoff value below which a clinical pregnancy may rarely be obtained after in vitro fertilization (IVF) [10,11]. Differently, other studies described ongoing pregnancies after IVF even in patients with low [12,13] or extremely low AMH levels (<0.1 ng/ml) [14], also including patients older than 40 [15].…”
Section: Introductionmentioning
confidence: 99%